(untitled) (Journal of the College of Basic Education, 2024)
This study aims to : 1- Identifying the effectiveness of the Rayan model in the achievement of the students of the Faculty of Fine Arts in the subject of appreciation and art criticism . 2- Identifying the complex thinking skills that must be developed among the students of the Faculty of Fine Arts . 3- Measuring the size of the effectiveness of designing courses related to complex thinking according to the Ryan model. The researcher used the experimental approach to achieve the objectives and hypotheses of the research and to suit the conditions and needs of the research . The sample was intentionally chosen for the students of the fourth stage, the College of Fine Arts - University of Babylon, and the number of the sample was (60) male and female students. The researcher distributed the research sample randomly into two groups (control - experimental). ) by lottery, and the number of the sample for each group was (30). The researcher was keen on equivalence of the sample with the following variables (the chronological age of the students _ previous experience _ intelligence _ the pre-compound thinking test - the academic achievement of the parents). The statistical data were processed through (the spss statistical bag. The following results showed: The students of the experimental group, who were applied to the content of the teaching plans that were prepared according to the Ryan model, outperformed their peers in the control group in the post-achievement test. Interpretation, analysis and conclusion. The researcher noticed the presence of interaction by the learners while receiving information, and this gives a positive indicator in acquiring and developing experiences in the subject of taste, art criticism and complex thinking skills. The members of the experimental group in the post-test excelled in acquiring the post-test complex thinking skills over their peers in the control group, and this is due to the nature of the lesson steps and the features of the model that focus on learning concepts and acquiring new experiences and information . It is clear from Table ( 20 ) that the Rayan model has an effectiveness in developing taste and artistic criticism in the post-test of the experimental group. By the pre-test of the same sample, which means that there is an effectiveness of this model in tasting and art criticism.